The Metacognitive Strategy of Chemistry Teacher Candidates in Chemistry Reading Activity - Benny Yodi Sawuwu (SEAQIS Journal of Science Education, 2021)
This qualitative study was conducted to explore the metacognitive strategy of chemistry teacher candidates in reading activities of a chemical article. There were 15 female chemistry teacher candidates voluntarily on this research from a public university. A chemical article that fulfilled some characteristics was used to stimulate the metacognitive activity, and 25 open-ended questions were posed for self-interviewing to reveal the metacognitive aspects. A think-aloud protocol was conducted during the reading activity. All reading activities were recorded and transcripted. Transcription of the think-aloud activity was considered to the reading rate to classify the think-aloud style into less think-aloud, formal think-aloud, and critical think-aloud. The reading pattern and data from self-interview showed that these three styles of think-aloud had different strategies on chemistry reading activity. The planning and evaluating activity determined the strategy chosen on reading. The monitoring activity was contributed by terms and chemical representatives used on the article.